Emendations in Valerius Flaccus, Argonautica book 4 - Kayachev, Boris (My University, 2024)
The paper tackles about a dozen passages from book 4 of Valerius’ Argonautica, arguing that the poem’s text remains full of unsolved problems.
PUBLISHED
Keywords: Latin poetry; textual criticism; Hylas; Prometheus; Amycus; Io; Phineus; Harpies; Symplegades; Manuscript, Book and Print Cultures; Language and/or Literature, Classical Latin; Latin poetry